Proposal of a methodology for oral health status analysis in dental studies - Diego Alfredo Ochoa González; Rosa María Gonzalés Ramos; Orietta Valverde GrandalValve (Editorial Ciencias Médicas, 2020)
Introduction: Health status analysis is an indispensable topic in the training of professionals who will be in charge of health in a community and as such require a useful tool to identify health problems in primary care. Objective: Describe a methodology to facilitate oral health status analysis in a community. Methods: A bibliographic review was conducted in the search engine Google Scholar and the databases PubMed, Lilacs, Cumed and SciELO Cuba. The review also covered the papers presented at the International Dental Congress 2015. The search terms used were 'health status', 'oral health', 'population health', 'primary health care', 'dental education' and their counterparts in Spanish. After filtering the results obtained, 49 scientific publications were selected due to their relationship to the subject and their topicality. Discussion: Health status analysis serves as a scientific methodological tool to identify, prioritize and solve community problems. The analytical stage is the most complex in the study and the one in which difficulties arise related to its orderly processing. The starting point should be the epidemiological classification of the study population, and a logical order should be followed in its conduct. Conclusions: A methodology is presented which facilitates identification and prioritization of substantial risks during the analytical stage of an oral health status analysis.